2016
DOI: 10.20944/preprints201611.0110.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impacts of Capital Structure on Performance of Banks in a Developing Economy: Evidence from Bangladesh

Abstract: Capital structure decision plays an imperative role in firm’s performance. Recognizing the importance, there has been many studies inspected the rapport of capital structure with performance of firms and findings of those studies are inconclusive. In addition, there is relative deficiency of empirical studies examining the link of capital structure with performance of banks in Bangladesh. This paper attempted to fill this gap. Using panel data of 22 banks for the period of 2005-2014, this study empir… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 14 publications
(37 reference statements)
7
31
0
Order By: Relevance
“…Based on the studies indicates that effect of return on asset (ROA) on bank profitability. These empirical findings are supported by the researchers [8][9][10]. Taani [10] found that the correlation between capital structure and performance of Jordanian bank is positively from 2007 to 2011.…”
Section: Literature Reviewsupporting
confidence: 56%
“…Based on the studies indicates that effect of return on asset (ROA) on bank profitability. These empirical findings are supported by the researchers [8][9][10]. Taani [10] found that the correlation between capital structure and performance of Jordanian bank is positively from 2007 to 2011.…”
Section: Literature Reviewsupporting
confidence: 56%
“…The adjusted R-squared of 0.47 indicates that 47% in the variation of return on asset is explained by debt to equity ratio, asset tangibility and age. On a whole, the results does not conform with the a priori expectation and it is also supported by the work of [27,29,25,32,16,11,30,31,33,14,35]. It is therefore established that capital structure has a negative influence on Bank performance and brings no improvement to the wealth of shareholders.…”
Section: Panel Regression Resultsmentioning
confidence: 75%
“…For instance, Siddik, Kabiraj et al [14] concluded the data of 22 banks over a period of 2005-2014 and observed capital structure have negative effect on return on equity, for data analysis used the least square technique.…”
Section: Empirical Evidencesmentioning
confidence: 99%
“…The ability of the Company to impose greater control over elements of the capital structure through its administrative control resulting from the preference of long-term financing owners to borrow instead of issuing new shares so as not to lose part of their control of the company to new shareholders (Siddik, et al, 2016).…”
Section: B) Repayment Capacitymentioning
confidence: 99%
“…Using panel data of 22 banks for the period of2005-2014 (Siddik, et al, 2016) explain that Capital structure decision plays an imperative role in firm's performance. Recognizing the importance, there has been many studies inspected the rapport of capital structure with performance of firms and findings of those studies are inconclusive.…”
Section: Literature Reviewmentioning
confidence: 99%